Primary synovial sarcoma of the lung: a rare presentation, diagnostic dilemma and review of literature. Issue 11 (23rd November 2020) - Pandey, Laxman; Joseph, Deepa; Pasricha, Rajesh; Gupta, Manoj Kumar
Abstract : Primary synovial sarcoma of the lung (PSSL) is a rare tumour with only 0.5% incidence among other primary malignant lung tumours. Published medical literature regarding the natural history treatment protocol and clinical outcomes of PSSL remains limited. Here, we present a case of a 39-year-old man with primary synovial sarcoma with long-term follow-up, which was initially viewed as a metastasis from another unknown site. After evaluating histopathologically from the specimen post left lung metastasectomy and ruling out any other site for neoplastic changes, the diagnosis of PSSL was confirmed. Furthermore, this article reviews the literature and discusses various aspects of PSSL, including clinical presentation, radiological imaging and pathological characteristics, diagnostic dilemma, management and prognosis. This paper serves to provide an update and aims to enhance the understanding of PSSL. Timely diagnosis and treatment are imperative to achieve improved outcomes.